2023
DOI: 10.1155/2023/6028554
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Lianhua Qingwen Capsules for COVID‐19: A Propensity‐Score Matched Cohort Study

Abstract: As a traditional Chinese medicine, Lianhua Qingwen capsules have been widely used to treat Coronavirus Disease 2019 (COVID-19). This study was aimed to demonstrate the association between treatment with Lianhua Qingwen capsules and the clinical outcomes of hospitalized patients with COVID-19. This retrospective study was conducted at four hospitals in Central China. Data of hospitalized COVID-19 patients were collected between December 19, 2019 and April 26, 2020. Based on whether Lianhua Qingwen capsules were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Prior research in the field has predominantly concentrated on assessing the effectiveness of LHQW in ameliorating clinical symptoms, with limited insights into its impact on VS ( 11–13 , 15 , 16 , 18 , 19 ). For instance, Academician Zhong’s recent publication reports findings from an international, multicenter, double-blind, randomized controlled study, primarily focusing on the alleviation of COVID-19 symptoms by LHQW, encompassing nasal congestion, sore throat, cough, fever, and other related symptoms ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research in the field has predominantly concentrated on assessing the effectiveness of LHQW in ameliorating clinical symptoms, with limited insights into its impact on VS ( 11–13 , 15 , 16 , 18 , 19 ). For instance, Academician Zhong’s recent publication reports findings from an international, multicenter, double-blind, randomized controlled study, primarily focusing on the alleviation of COVID-19 symptoms by LHQW, encompassing nasal congestion, sore throat, cough, fever, and other related symptoms ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…These distinctions in both the viral variants and the study populations were pivotal in understanding the differing outcomes observed. Conversely, another study encompassing a large adult population of 4,918 cases demonstrated that the LHQW treatment group exhibited improvements in the nucleic acid conversion rate ( 19 ). Numerous systematic reviews and meta-analyses have underscored the substantial efficacy of LHQW in the treatment of COVID-19 ( 14 , 15 , 22 ), reporting enhancements in clinical symptoms and a reduction in the progression to severe or critical conditions, but they did not specifically monitor VS.…”
Section: Discussionmentioning
confidence: 99%